Oviposition, larval preference, and larval performance in two polyphagous species: does the larva know best?. Issue 1 (27th August 2014) - Gómez Jiménez, María Isabel; Sarmiento, Carlos E.; Díaz, María Fernanda; Chautá, Alexander; Peraza, Andrés; Ramírez, Augusto; Poveda, Katja
Abstract It is expected that females preferentially oviposit on plant hosts that allow for optimal larval performance. However, this expectation contradicts empirical evidence where adults do not always choose the best host for their descendants. Recent evidence suggests that females' host selection depends on the number of potential hosts. Females from oligophagous species seem to be able to choose an appropriate host in terms of larval performance, whereas in polyphagous species, adult oviposition preference is not related with larval performance. This suggests that larvae in polyphagous species could be taking a more active role in host selection than their mothers. Here, we evaluated the oviposition preference and the larval preference and performance of two polyphagous species of economic importance, Copitarsia decolora (Guenée) (Lepidoptera: Noctuidae: Cuculliinae) and Peridroma saucia (Hübner) (Lepidoptera: Noctuidae: Noctuinae), on eight species of cultivated plants. In laboratory and greenhouse choice assays, we tested adult preference for oviposition and larval preference at 1 and 24 h. Larval performance was measured in terms of survival to adulthood, length of larval period, and pupal weight. We found that both adult females and larvae actively choose their hosts and that the larval preference toward the hosts is related to the females' preference in both herbivore species. However, the females and larvae did not preferentially select the host with the best larval performance, indicating that larval performance is not related to female or larval preference and that other selective pressures are influencing the choice of the host plant in these two species.